Curriculum evaluation of technical vocational training - Gordon, Kenneth William (2009)
This thesis is a Case Study of a professional technical training programme designed for an Executive Agency of a major government department. The purpose was to explore the structure, strengths and weaknesses of the programme and to put forward useful suggestions for improvement. The personnel recruited into the programme are experienced technical specialists, often accustomed to the exercise of considerable responsibility and authority, earlier in their careers. The programme is intended to impart the extra skills required in their new role. There is special emphasis on assessment of student learning and curriculum evaluation and the possible confusion between the two terms. The problem of Outcomes and how the competency of the trainees is to be judged is considered. Also considered are learning styles, content and the teaching environment.